2004
DOI: 10.1186/1741-7015-2-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled trial of prednisone in early Henoch Schönlein Purpura [ISRCTN85109383]

Abstract: Background: Henoch Schönlein Purpura (HSP) is the most common systemic vasculitis of childhood. There is considerable controversy over whether children with HSP should be treated with corticosteroids. The goal of this study was to investigate whether early corticosteroid administration could reduce the rate of renal or gastrointestinal complications in children with HSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(92 citation statements)
references
References 22 publications
2
76
0
13
Order By: Relevance
“…Sano et al Other randomized and placebocontrolled trials have also found that the use of prednisone at the start of HSP does not avert kidney damage. 14,15 In our patients sample it was demonstrated that use of corticosteroids was associated with greater renal involvement, since these patients exhibited a greater frequency of severe gastrointestinal involvement and required these medications. These were habitually introduced during the first month of the disease and were predominantly indicated to control significant gastrointestinal manifestations, such as intermittent and severe abdominal pain in colic, and bleeding and intussusception.…”
Section: Discussionmentioning
confidence: 67%
“…Sano et al Other randomized and placebocontrolled trials have also found that the use of prednisone at the start of HSP does not avert kidney damage. 14,15 In our patients sample it was demonstrated that use of corticosteroids was associated with greater renal involvement, since these patients exhibited a greater frequency of severe gastrointestinal involvement and required these medications. These were habitually introduced during the first month of the disease and were predominantly indicated to control significant gastrointestinal manifestations, such as intermittent and severe abdominal pain in colic, and bleeding and intussusception.…”
Section: Discussionmentioning
confidence: 67%
“…A systematic review, including three prospective, randomized, placebo-control trials and 12 retrospective trials, analyzed the efficacy of CS for HSP and found that early CS treatment at the onset of HSP significantly reduced the odds of developing persistent kidney disease (Weiss et al, 2007). However, these studies did not take account of the effects of CS on proteinuria or remission of HSPN and no ACEI or ARB was used as a control (Mollica et al, 1992;Saulsbury, 1993;Huber et al, 2004;Ronkainen et al, 2006). Based on the RCT data for IgAN, the KDIGO Glomerulonephritis Work Group (2012) suggested a six-month course of CS for HSPN patients with persistent proteinuria greater than 1 g/24 h, after a trial of ACEI or ARB.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggested treating only patients with risk factors for renal involvement at disease onset [18,22]. Prednisone is often favored over methylprednisolone during pregnancy, as transplacental passage occurs in small amounts, reducing the risk of fetal adverse effects [2,23]. Among the 20 cases of HSP during pregnancy, half were treated with steroids, leading to rapid resolution of purpura, abdominal symptoms or arthralgia [6].…”
Section: Discussionmentioning
confidence: 99%